Persistent mortality in critical COVID-19 ICU cases from wild-type to delta variant: a descriptive cohort study - Palmowski, Lars; Hagedorn, André; Witowski, Andrea; Haberl, Helge; Kraft, Felix; Achtzehn, Ute; Kindgen-Milles, Detlef; Zacharowski, Kai; Nierhaus, Axel; Dietrich, Maximilian; Mirakaj, Valbona; Koch, Thea; et al. (Scientific reports, 2025)
The SARS-CoV-2 pandemic led to significant advancements in treatment and vaccination, contributing to a decline in overall COVID-19-related mortality. However, it remains unclear whether the mortality rate for critical cases treated on intensive care units has also decreased. This multicentric, multinational retrospective observational study analyzed 447 critically ill COVID-19 patients treated on ICUs across ten study centers in Germany and Austria. Patients were categorized into two periods: period 1 (March 2020 to May 2021, n = 316) and period 2 (June 2021 to January 2022, n = 131). Despite evolving treatment strategies and widespread vaccine availability in period 2, 30-day mortality remained unchanged (30% in period 1 vs. 37% in period 2; HR 1.26, 95% CI: 0.90-1.79, p = 0.181). Further outcomes, including ICU-free days (p = 0.735), ventilatory support-free days (p = 0.699), vasopressor-free days (p = 0.379), and dialysis-free days (p = 0.396), also showed no significant differences. Notably, 81% (106 of 131) of ICU patients in period 2 were unvaccinated, underscoring the persistent vulnerability of this group. These findings suggest that while public health measures reduced overall COVID-19 severity, critical illness remained highly lethal. Further research is needed to explore targeted interventions for high-risk ICU patients and to better understand the factors contributing to persistent mortality despite medical advancements.